Developing Students’ Writing Skills Through Short Story in ELT - Fitri, Levita Zuhrotul; Adam, Aidin; Rohmana, Wahyu Indah Mala (Universitas Islam Negeri (UIN) Mataram, 2024)
This study examines the effect of the appearance-based approach in enhancing students' short story writing skills at MA Model Zainul Hasan. The research highlights challenges such as low literacy rates and limited English vocabulary, particularly in Islamic boarding schools, which hinder students’ writing development. The study aims to address these issues by integrating innovative methods to improve literacy and writing skills. Using a qualitative descriptive method, data were collected through classroom observations and interviews. The findings reveal that the appearance-based approach significantly enhances students' ability to organize and express ideas creatively. It also boosts their confidence in public speaking through storytelling exercises. Furthermore, the method fosters collaboration among students and supports the development of critical thinking and creativity. The study concludes that short story writing, supported by appearance-based techniques, is an effective strategy for overcoming language barriers and improving literacy. The implications suggest that educators should adopt similar innovative approaches to nurture students' motivation, creativity, and engagement in writing activities. This research contributes to the development of practical teaching strategies in contexts with limited exposure to English.